Learning for Generation Alpha in Early Character Development: A Case Study - Salsa Annabila, Azzahro’; Pricilla Madonda, Nompumelelo; Samuel Jacob, Udeme; Aulia, Raina; Saskiyah, Fanny; Nurul Aini, Fiddini; Ni’mathush Solehah, Rizka (Nak-Kanak: Journal of Child Research, 2025)
Background of the study: Early childhood (ages 0–6) is considered the golden age of human development, when children can easily absorb and imitate knowledge from their surroundings. At this critical stage, character education is vital and should be implemented by both teachers and parents as primary educators. Character formation is shaped not only by genetic factors but also by environmental influences, particularly education. Consistent and systematic character education fosters positive values that can last into adulthood. Aims and scope of paper: This paper examines strategies for stimulating character education in Generation Alpha students at TK Hang Tuah 13, focusing on the roles of teachers and parents. It explores four core methods and twelve specific strategies for early childhood character formation, integrating theoretical foundations with practical insights from field interviews. Methods: Using a qualitative case study design, the research involved teachers, students, and parents selected through purposive sampling. Data were gathered over three months via in-depth interviews, classroom observations, and document analysis, supported by field notes and audio recordings. Thematic analysis followed Braun and Clarke’s framework, with trustworthiness ensured through member checking, peer debriefing, and triangulation. Results: Character education at TK Hang Tuah 13 is implemented holistically, guided by the Buku 9 Pilar Karakter and the K4 concept. Values such as honesty, responsibility, discipline, independence, creativity, cooperation, tolerance, and nationalism are instilled through daily habituation, role modeling, structured projects, and outdoor activities. Findings show growth in moral, performance, and social character. The program positively impacted both school and home environments, supported by strong collaboration between teachers and parents. Contribution: The study offers a structured framework for Generation Alpha character education, bridging theory and practice. It underscores the importance of sustained school–home partnerships in shaping children’s moral and social values during the formative years.